2008
DOI: 10.1016/j.bbrc.2008.01.165
|View full text |Cite
|
Sign up to set email alerts
|

Trim11 increases expression of dopamine β-hydroxylase gene by interacting with Phox2b

Abstract: The homeodomain transcription factor Phox2b is one of the key determinants involved in the development of noradrenergic (NA) neurons in both the central nervous system (CNS) and the peripheral nervous system (PNS). Using yeast two-hybrid screening, we isolated a Phox2b interacting protein, Trim11, which belongs to TRIM (Tripartite motif) or RBCC proteins family, and contains a RING domain, B-boxes, a coiled-coil domain, and the B30.2/SPRY domain. Protein-protein interaction assays showed that Phox2b was able t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Deletion of the SPRY domain in TRIM11, TRIM21, and TRIM25 abrogated the interaction of the proteins with their binding partner proteins. 26,32,33 In this study we found that the SPRY domain was essential for the nuclear localization of TRIM22, and TRIM22 lacking the SPRY domain was localized exclusively to the cytoplasm of HepG2 cells and lost its suppressive activity on HBV CP. As no nuclear localization signal (NLS) is found in the SPRY domain of TRIM22 and the SPRY domain has often been implicated in protein-protein interactions, we suspect that TRIM22 may be transported into the nucleus by binding to other nuclear proteins through its SPRY domain.…”
Section: Discussionmentioning
confidence: 53%
“…Deletion of the SPRY domain in TRIM11, TRIM21, and TRIM25 abrogated the interaction of the proteins with their binding partner proteins. 26,32,33 In this study we found that the SPRY domain was essential for the nuclear localization of TRIM22, and TRIM22 lacking the SPRY domain was localized exclusively to the cytoplasm of HepG2 cells and lost its suppressive activity on HBV CP. As no nuclear localization signal (NLS) is found in the SPRY domain of TRIM22 and the SPRY domain has often been implicated in protein-protein interactions, we suspect that TRIM22 may be transported into the nucleus by binding to other nuclear proteins through its SPRY domain.…”
Section: Discussionmentioning
confidence: 53%
“…These observations indicate that the HIV-1 LTR harbors specific sequences required for TRIM22 inhibitory effects. In this regard, TRIM22, as well as other TRIM family members, has not yet been credited with the capacity to directly interact with DNA (29,76,77), whereas several host transcription factors, including NF-B, NFAT-1, AP-1, Sp1, STAT5, and others (15,20,35,45,72), could be direct or indirect targets of TRIM22-mediated transcriptional inhibition of the HIV-1 LTR. In accordance also with the insensitivity of the CMV promoter, known to be mainly regulated by the NF-B activation cascade (30,42), in 293T cells and with the lack of net suppressive effects on TNF-␣-driven transcription of the HIV-1 LTR, we indeed observed that TRIM22 antiviral activities were independent of the tandem NF-B binding element within the core enhancer region of the viral promoter.…”
Section: Discussionmentioning
confidence: 99%
“…TRIM11 also binds to and mediates the ubiquitination of PAX6 (paired box 6), a member of the PAX family of transcription factors and plays a key role in organogenesis of the eye, pancreas, and brain (23). Finally, TRIM11 is involved in the specification of noradrenergic (NA) phenotype by interacting with Phox2b, a homeodomain transcription factor that could modulate development of NA neurons (24). These findings implicate an important, albeit still incompletely defined, role of TRIM11 in nervous system function and development.…”
Section: Introductionmentioning
confidence: 99%